Genetic variations of East Kalimantan Orangutan based on D-Loop mitochondria DNA - DIDIK PRASETYO; JITO SUGARDJITO (Biodiversitas Journal of Biological Diversity, 2007)
Analysis of the variation of D-Loop mtDNA of East Kalimantan orangutan was done to provided the genetic information data from endangerd species in order to support their population conservation efforts. The reason using mtDNA in this research is caused by higher level of mutation ( 5 â€“ 10 trimes) when compared with nuclear DNA and it enable to transmited via maternal transmission without experience in recombination. From the analysis conducted on 38 samples resulting eight types of haplotype that is A, B, C, D, E, G, H and I haplotype. Level of variation of the haplotype at East Kutai district was more uniform when compared by variation in Kutai district. From the paternal analysis had been got three cluster with the nearer among cluster IADG and cluster EH compared by cluster BC. Dissociation timebetween haplotype are 250.000-400.000 years ago, and known the population of East Kalimantan orangutan separated from Sumatran orangutan (X97708) since 1.158.300 years ago.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: , D-Loop mtDNA, East Kalimantan